Hubungan Persepsi Siswa terhadap Konselor dan Sarana Prasarana Bimbingan Konseling dengan Minat Layanan Konseling - Cut Ita Zahara; Lahmuddin Lubis; Azhar Aziz (Universitas Medan Area, 2019)
This research is to know the relation of student perception to counselor and infrastructure facilities of Counseling Guidance with interest of counseling guidance service to students of SMP Negeri 2 Dewantara - Aceh Utara 2017. Type of research is quantitative. The research population of all students in grade VIII and IX SMP is 200 students. The sample of this study amounted to 109 students of SMP Negeri 2 Dewantara. Sampling technique in the form of simple random sampling and data collection method using psychological scale and questionnaire, while the method of data analysis using product moment correlation analysis. The results of this study indicate that (1) there is a significant positive correlation between students' perceptions on counselor and BK infrastructure with interest of counseling service, where coefficient rx12y = 0.662 and p = 0,000 with contribution equal to 43,9%. (2). There is a significant positive correlation between students' perceptions of counselors with interest in counseling counseling services, where the coefficients rx1y = 0.662 and p = 0,000 with contribution of 43.8%. (3). There is a significant positive relationship between BK facilities and infrastructure with the interest of counseling services, where the coefficient rx2y = 0.271 and p = 0,000 with a contribution of 7.3 % thus stated that all hypotheses are acceptable.